MEDICAL AND ENVIRONMENTAL ASPECTS EVOLUTION OF DISEASES OF THE ENDOCRINE SYSTEM IN CHILDREN OF UKRAINE - Volosovets, О.P.; Кryuchko, T.O.; Marushko, Yu.V.; Lezhenko, G.A.; Volosovets, T.M.; Kryvopustov, S.P.; Dіkova, I.G. (World of Medicine and Biology, 2023)
We have found that in 2017 9.569 cases of endocrine system diseases were detected in children affected by the Chornobyl accident (or 24,67 per 1.000 children), which is by 1.7 times higher than the mean incidence of this pathology in children in Ukraine. Мethods of statistical evaluation and epidemiological analysis of state medical statistics from 1993 to 2020 were used.Throughout 25 years of observation we have discovered that from the period of 1993 to 2017 was a decrease in the incidence and prevalence of the endocrine system diseases in children by 36.9 %, and, more significantly, by 65.5 % – in children who suffered as a result of the Chernobyl accident. At the same time, disability increased by 5.3 times. The prevalence and incidence of endocrine diseases in children affected by the Chernobyl accident are significantly higher than the national mean, especially in the detection of thyroid disease.
Keywords: сhildren; morbidity; prevalence; disability; diseases of the endocrine system; Chornobyl disaster